Prosthetic rehabilitation of ocular defect - Natarajan Kalavathy; Janakirama Reddy Sridevi; Archana K Sanketh; Rohan Yadav; D H Chandravathi (Wolters Kluwer Medknow Publications, 2014)
The loss of a part of the face, particularly the eye, requires early replacement and hence that the patient may return to a normal life. The maxillofacial defect causes esthetic, functional, and psychological difficulties for the patient. Although most ocular prostheses can be made from a prefabricated artificial eye, customized ocular prostheses offer better esthetics. This article describes the fabrication of a custom ocular prosthesis where a prefabricated iris was modified to fit into a custom-made scleral portion of prostheses. The time for fabrication of prosthesis was less and good esthetics was achieved.